Business cycle dynamics under rational inattention - Bartosz Maćkowiak; Mirko Wiederholt (European Central Bank (ECB), 2011)
We develop a dynamic stochastic general equilibrium model with rational inattention by households and firms. Consumption responds slowly to interest rate changes because households decide to pay little attention to the real interest rate. Prices respond quickly to some shocks and slowly to other shocks. The mix of fast and slow responses of prices to shocks matches the pattern found in the empirical literature. Changes in the conduct of monetary policy yield very different outcomes than in models currently used at central banks because systematic changes in policy cause reallocation of attention by decision-makers in households and firms.
Keywords: D83; E31; E32; E52; 330; business cycles; information choice; monetary policy; rational inattention